Frequent CDKN2B/P15 and DAPK1 methylation in duodenal follicular lymphoma is related to duodenal reactive lymphoid hyperplasia - Sato, Yasuharu; Takata, Katsuyoshi; Miyata-Takata, Tomoko (Journal of Clinical and Experimental Hematopathology, 2024)
Duodenal type follicular lymphoma (DFL), a rare entity of follicular lymphoma (FL), is clinically indolent and is characterized by a low histological grade compared with nodal follicular lymphoma (NFL). Our previous reports revealed that DFL shares characteristics of both NFL and mucosa-associated lymphoid tissue (MALT) lymphoma in terms of clinical and biological aspects, suggesting its pathogenesis may involve antigenic stimulation. In contrast to NFL, the genomic methylation status of DFL is still challenging. Here, we determined the methylation profiles of DNAs from patients with DFL (n = 12), NFL (n = 10), duodenal reactive lymphoid hyperplasia (D-RLH) (n = 7), nodal reactive lymphoid hyperplasia (N-RLH) (n = 5), and duodenal samples from normal subjects (NDU) (n = 5) using methylation specific PCR of targets previously identified in MALT lymphoma (CDKN2B/P15, CDKN2A/P16, CDKN2C/P18, MGMT, hMLH-1, TP73, DAPK, HCAD). DAPK1 was frequently methylated in DFL (9/12; 75%), NFL (9/10; 90%), and D-RLH (5/7; 71%). CDKN2B/P15 sequences were methylated in six DFL samples and in only one NFL sample. Immunohistochemical analysis showed that p15 expression inversely correlated with methylation status. Genes encoding other cyclin-dependent kinase inhibitors (CDKN2A/P16, CDKN2C/P18) were not methylated in DFL samples. Methylation of the genes of interest was not detected in DNAs from D-RLH, except for DAPK1, and the difference in the extent of methylation between NDU and D-RLH was statistically significant (P = 0.013). Our results suggest that D-RLH serves as a reservoir for the development of DFL and that methylation of CDKN2B/P15 plays an important role in this process.